2017
DOI: 10.1007/s10714-017-2196-9
|View full text |Cite
|
Sign up to set email alerts
|

Horizonless, singularity-free, compact shells satisfying NEC

Abstract: Gravitational collapse singularities are undesirable, yet inevitable to a large extent in General Relativity. When matter satisfying null energy condition (NEC) collapses to the extent a closed trapped surface is formed, a singularity is inevitable according to Penrose's singularity theorem. Since positive mass vacuum solutions are generally black holes with trapped surfaces inside the event horizon, matter cannot collapse to an arbitrarily small size without generating a singularity. However, in modified theo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…THEDgravity presents a simple solution by preventing the extreme inhomogeneity-buildup into black holes. It has been shown that there can exist extremely compact objects that does not violate the NEC [22], which would otherwise be expected to collapse into black holes in the context of GR. That is, finite pressure can restrain the gravitational collapse of a massive object even after it has shrunk to an arbitrarily small size, thus preventing the formation of singularity while leaving the exterior geometry virtually indistinguishable from that of a black hole.…”
Section: B Bounded Oscillating Universementioning
confidence: 99%
“…THEDgravity presents a simple solution by preventing the extreme inhomogeneity-buildup into black holes. It has been shown that there can exist extremely compact objects that does not violate the NEC [22], which would otherwise be expected to collapse into black holes in the context of GR. That is, finite pressure can restrain the gravitational collapse of a massive object even after it has shrunk to an arbitrarily small size, thus preventing the formation of singularity while leaving the exterior geometry virtually indistinguishable from that of a black hole.…”
Section: B Bounded Oscillating Universementioning
confidence: 99%